2019
DOI: 10.3390/ijerph16224587
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic Characteristics of Traditional Healers and Their Knowledge of Noma: A Descriptive Survey in Three Regions of Mali

Abstract: Background: Noma can be a lethal disease and causes disfigurement in young children in low-resource countries, particularly in Africa. In these settings, 80% of the population mainly consult traditional healers for healthcare problems. Our study aimed to describe the sociodemographic characteristics of traditional healers and to assess their knowledge of noma. Methods: We conducted a survey among traditional healers in three Malian regions from May 2015 to January 2016 and collected data on sociodemographic ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 21 publications
1
20
1
Order By: Relevance
“…Likewise, many studies also found that the traditional healers are generally above 50 years old (Muthee et al 2011;Baratti-Mayer et al 2019). In our earlier studies, we also observed that most of the informants having anthelmintic ethnomedicinal information from three districts Udalguri, Baksa and Udalguri of BTR, were above 50 years old (Swargiary et al 2019a, b;Swargiary et al 2020).…”
Section: Discussionsupporting
confidence: 62%
“…Likewise, many studies also found that the traditional healers are generally above 50 years old (Muthee et al 2011;Baratti-Mayer et al 2019). In our earlier studies, we also observed that most of the informants having anthelmintic ethnomedicinal information from three districts Udalguri, Baksa and Udalguri of BTR, were above 50 years old (Swargiary et al 2019a, b;Swargiary et al 2020).…”
Section: Discussionsupporting
confidence: 62%
“…In Mali and Nigeria, traditional healers’ knowledge of noma was limited [ 126 , 146 ], however, several traditional healers in Nigeria reported treating different stages of the disease. In Nigeria, traditional treatments for noma include ground herbs, plants, ointments and piercing of the swollen cheek (in the oedema phase of noma) [ 126 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nowadays noma affects the most impoverished children in remote areas where there are no records of births or deaths. Primary healthcare workers and traditional healers often do not recognize noma [3,14]. Noma is not taught in medical schools either in the occidental world or in the countries concerned.…”
Section: Why Is Noma Neglected?mentioning
confidence: 99%